2017
DOI: 10.3389/fgene.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, DNA Damage, Helicobacter pylori and Gastric Tumorigenesis

Abstract: Helicobacter pylori (H. pylori) is a Gram negative bacterium that colonizes the stomach of almost half human population. It has evolved to escape immune surveillance, establishes lifelong inflammation, predisposing to genomic instability and DNA damage, notably double strand breaks. The epithelial host cell responds by activation of DNA damage repair (DDR) machinery that seems to be compromised by the infection. It is therefore now accepted that genetic damage is a major mechanism operating in cases of H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 104 publications
(119 reference statements)
1
41
0
3
Order By: Relevance
“…During H. pylori infection, the adaptive immune response is usually associated with T helper cells (Th‐1 cells and Th‐17 T cells) that induce the secretion of IL‐17 and INFγ after inducing inflammation and cell damage. The impaired modulation of Th‐1 and Th‐17 cells is hypothesized for ongoing or long‐term infection . VacA was primarily identified because of its ability to induce vacuolization of epithelial cells.…”
Section: Ureasementioning
confidence: 98%
See 1 more Smart Citation
“…During H. pylori infection, the adaptive immune response is usually associated with T helper cells (Th‐1 cells and Th‐17 T cells) that induce the secretion of IL‐17 and INFγ after inducing inflammation and cell damage. The impaired modulation of Th‐1 and Th‐17 cells is hypothesized for ongoing or long‐term infection . VacA was primarily identified because of its ability to induce vacuolization of epithelial cells.…”
Section: Ureasementioning
confidence: 98%
“…The impaired modulation of Th-1 and Th-17 cells is hypothesized for ongoing or long-term infection. 107,110 VacA was primarily identified because of its ability to induce vacuolization of epithelial cells. Later on, it has been reported that VacA also inhibits T-cell proliferation by downregulating the level of IL-2.…”
Section: Inhibition Of Th-1-and Th-17-mediated Immunological Responsesmentioning
confidence: 99%
“…Infection‐related cancer is caused either directly by tumorigenic effects of the pathogen or indirectly through accompanying inflammation and subsequent genomic instability . H pylori has the ability to induce a chronic immune response, including persistent oxidative stress in the stomach, resulting in DNA damage .…”
Section: Dna Damage: a New Perspective To Understand Helicobacter Pylmentioning
confidence: 99%
“…Upon recognition of H pylori , both innate and adaptive host responses are activated during the infection. Neutrophils and macrophages, as well as gastric epithelial cells, trigger ROS and RON production and create oxidative stress . The goal of ROS production by the host cells is to limit the development of pathogens.…”
Section: Dna Damage: a New Perspective To Understand Helicobacter Pylmentioning
confidence: 99%
See 1 more Smart Citation